An Indian Folkore Phytomedicine Perilla frutescens L.: Free Radical Scavenging Property along with Metal Detection by ICP-MS - Singh, Ajay; Kumar Dixit, Arunesh; Farooq, S.; Mehmood, Zafar; Lata Chhimwal, Suman (Asian Journal of Chemistry, 2021)
In present study, free radical scavenging activity of methanolic extract of all parts (leaves, seeds, root, stem and flower) of Perilla frutescens L. has been estimated. The promising results, among the five plant parts leaves, seeds, root, stem, flower and the standard tested for the in vitro antioxidant activity using the DPPH method, the crude methanolic extracts of all parts showed antioxidant activity, with IC50 values of 5.95 ± 0.10, 8.28 ± 0.20, 66.27 ± 0.17, 80.03 ± 0.10 and 122.35 ± 0.17 μg/mL, respectively. The IC50 value for ascorbic acid was 5.19 ± 0.26 μg/mL. While butylated hydroxyl toluene (BHT) a synthetic commercial antioxidant has comparatively high IC50 value of 108.46 ± 0.57 μg/mL. Presence of zinc in all parts of plant in the range 17.20 ± 0.22 to 33.56 ± 0.32 ppm further supports the strong antioxidant activity of Perilla frutescens L. The phytochemical tests indicated that all parts of Perilla frutescens L. have considerable proportion of important phytochemicals and are in rich source of secondary metabolites like polyphenols, tannins, alkaloids and flavonoids. Several of such compounds are known to possess potent antioxidant activity.